First identification of genotypes of Enterocytozoon bieneusi (Microsporidia) among symptomatic and asymptomatic children in Mozambique - Muadica, Aly S.; Messa, Augusto E., Jr.; Dashti, Alejandro; Balasegaram, Sooria; Santin, Mónica; Manjate, Filomena; Chirinda, Percina; Garrine, Marcelino; Vubil, Delfino; Acácio, Sozinho; Köster, Pamela C.; Bailo, Begoña; et al. (PLOS Neglected Tropical Diseases, 2020)
Author summary Enterocytozoon bieneusi is an obligate intracellular parasite that infects a wide range of vertebrate hosts. It is the most important etiological agent of human microsporidiasis. Most clinical and epidemiological studies conducted to date have focused on immunodeficient or immunosuppressed individuals including HIV+ patients and solid organ transplant recipients, as in those E. bieneusi infection causes life-threatening chronic diarrhoea. In contrast, latent microsporidia infections in immunocompetent individuals have received far less attention. Molecular epidemiological studies in humans and animals have revealed that E. bieneusi encompasses a very large diversity of genetic variants (genotypes) with marked differences in host specificity and even geographical distribution. In Mozambique, as in many other African countries, the epidemiology of E. bieneusi is completely unknown. Therefore, to identify the occurrence and genetic diversity of this pathogen in Mozambique stool samples were obtained from children, including apparently healthy and symptomatic, in Zambézia and Maputo provinces and tested for E. bieneusi by molecular methods. Results demonstrated the presence of E. bieneusi genotypes for the first time in Mozambique. Four genotypes were identified, three genotypes that have previously been reported in humans (Peru11, Type IV, and S2) and a novel genotype (HhMzEb1). Two of the genotypes Peru11, Type IV have also been frequently identified in animals indicating that potentially zoonotic E. bieneusi genotypes are inadvertently circulating in the surveyed populations. Additional population genetic studies are needed to elucidate the actual extent of the epidemiology and transmission dynamics of E. bieneusi in Mozambique.